Floral Neighbourhoods in the Sea: How Floral Density, Opportunity for Outcrossing and Population Fragmentation Affect Seed Set in Zostera marina - Reusch, Thorsten B. H. (The Journal of ecology, 2003)
1 Almost nothing is known about how the floral neighbourhood affects reproductive output in plants with subaqueous pollination (hydrophily), such as seagrasses, an ecologically important group of some 60 marine angiosperms. 2 I studied how floral density, genetic diversity and population fragmentation affect seed set in Zostera marina (eelgrass), a functionally hermaphrodite seagrass with extensive clonal propagation. 3 In a field experiment in the south-western Baltic Sea, I increased or decreased the density of flowering shoots in 6 × 6 m plots. Early seed set was a positive, saturation-type function of density suggesting pollen limitation below approximately 5 flowering shoots m-2. 4 Using molecular markers, I determined local genotypic diversity and outcrossing rates as indicators of outcrossing opportunities. I found only non-significant effects of these variables on early seed set, suggesting that density of the floral neighbourhood is more important than genetic composition. 5 Early seed set was 22% lower in isolated vegetation patches compared to continuous eelgrass meadow $(>50\ \text{m}^{2})$. 6 Given the spatial scale of the observed pollen limitation, and low natural densities of flowering shoots in the field, pollen limitation may be widespread in Z. marina and, possibly, other plant species with subaqueous pollination.